Pengaruh motivasi belajar terhadap hasil belajar matematika siswa kelas X SMA Negeri 1 Meluhu - Arsyantika, Nining; Hermanto; Hajeniati, Nining (Jurnal Pendidik Indonesia, 2023)
This study investigates the influence of learning motivation on the mathematics learning outcomes of 10th-grade students at SMA Negeri 1 Meluhu. The research method used is Ex-Post Facto, which aims to identify the cause-and-effect relationship between the independent variable (learning motivation) and the dependent variable (mathematics learning outcomes) after an event or phenomenon. The study population comprises 29 10th-grade students at SMA Negeri 1 Meluhu in the academic year 2021/2022, divided into two classes. The sample was selected using the Random Sampling method, ensuring that each individual in the population had an equal chance of being selected. Data were collected through a learning motivation questionnaire and mid-semester exam scores (UTS) recording. The research results indicate that learning motivation has a moderate influence on students' mathematics learning outcomes, with an average learning motivation score of 44. In contrast, students' mathematics learning outcomes fall within the moderate category, with an average score of 55. Simple linear regression analysis revealed that each one-point increase in student learning motivation contributes to a 0.782-point increase in mathematics learning outcomes. In conclusion, learning motivation significantly influences the mathematics learning outcomes of 10th-grade students at SMA Negeri 1 Meluhu, with learning motivation explaining approximately 68% of the variation in student learning outcomes.